Integrated proteomics and single-cell transcriptomics reveal potential therapeutic targets in Wilson’s disease patients - Qi, Yue; Sun, Minghui; Xu, Fang; Zhou, Hao; Yuan, Lihua; Yu, Xinlei; Cao, Sirui; Hua, Rui (Frontiers in Immunology, 2025)
PurposeWilson’s Disease (WD), an autosomal recessive ATP7B mutations disorder causing copper accumulation, poses diagnostic challenges. This study used proteomics and single-cell transcriptomics to identify WD mechanisms and therapeutic targets.MethodsProteomic analysis was conducted on clinical samples from WD patients and the control group, followed by validation via ELISA. Subsequently, an integrated analysis was conducted by combining these data with single-cell RNA sequencing data from the database. Analytical content included differential expression, functional enrichment, drug target prediction, immune infiltration, and subtype-specific biomarker screening via LASSO/SVM-REF.ResultsProteomic analysis identified 420 differentially expressed proteins (266 upregulated, 154 downregulated) in WD patients compared with healthy controls, with significant enrichment in inflammatory pathways. Integration with DrugBank revealed eight hub proteins with high diagnostic accuracy (AUC > 0.9), among which Inter-alpha-trypsin inhibitor heavy chain 1 (ITIH1) and Transthyretin (TTR) may regulate the PI3K-Akt signaling pathway. Subsequently, ELISA validation confirmed significantly reduced levels of TTR, Ceruloplasmin (CP), and ITIH1 proteins in WD. Considering the heterogeneity of the WD microenvironment and single-cell diversity, further single-cell transcriptomic analysis was performed. The results revealed immune dysregulation, characterized by increased macrophage infiltration and reduced T/NK cell proportions, and PI3K-Akt-mTOR pathway enrichment in macrophages. For subtype-specific analysis, six key proteins were identified to distinguish hepatic and brain subtypes (AUC > 0.9).ConclusionsThe hub proteins and subtype-specific biomarkers identified in this study provide potential targets for the precise treatment of WD, while emphasizing the critical role of the PI3K-Akt pathway in WD.